Pipeline accidents and incidents, environmental consciousness, and financial performance in the canadian energy industry - Denommee-Gravel, Vincent; Kim, Kyungho (Sustainability (Switzerland), 2019)
This study employs a balanced panel of data which consists of 1281 firm-year pipeline accidents and incidents at a disaggregate level and 190 firm-year pipeline events at an aggregate level for 19 firms during the observation period between 2007 and 2016. This study examines the relationships among environmental accidents and incidents, environmental consciousness, and financial performance. Given that environmental consciousness acts as an overarching environmental context on the relationship between the accidents, incidents, and financial performance and could be relevant to shareholders to identify the weight of these accidents and incidents, this study carefully investigates how environmental consciousness moderates the relationship between pipeline accidents, incidents, and financial performance. This study applies the theoretical assumption of both corporate social responsibility (CSR) and corporate social irresponsibility, both of which explain the relationship between financial performance and the events that positively or negatively affect stakeholders. This study employs nested regression analyses with the fixed effects model to test the time-series panel data. The results show that environmental consciousness has an expected significant negative effect on financial performance, whereas pipeline accidents and incidents have no expected negative effect on financial performance. One surprising finding is that pipeline accidents and incidents weighted with environmental consciousness present a significant positive relationship with financial performance, suggesting that potential contextual factors should be considered to explain such an unexpected finding.
Keywords: Environmental consciousness; Financial performance; Pipeline accidents and incidents